Job Satisfaction Moderated Burnout, Work-Life Balance, And Lecturer Performance During The Industrial Revolution 4.0. - Ilham, Ilham; Olle, Andi Tenri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Objective: This study investigates the moderating role of job satisfaction in the relationship between burnout, work-life balance, and lecturer performance in the era of Industrial Revolution 4.0. This methodology/approach uses a quantitative approach with purposive sampling and partial least squares (PLS) analysis. Using a quantitative research design, a cross-sectional survey was conducted to collect data from the university lecturers. Standard questionnaires were used to measure job satisfaction, burnout, work-life balance, and lecturer performance. Data will be collected through an online survey platform with a minimum response rate of 70%, involving 121 random permanent lecturers from various private universities at the Higher Education Service Institution (LLDIKTI) Region IX Sulawesi. Descriptive statistics were used to summarize the data, and inferential statistics were tested using the partial least squares (PLS) hypothesis. Findings – Burnout did not significantly affect lecturer performance, while a higher work-life balance led to increased job satisfaction. Increased burnout reduces lecturer performance, but work-life balance has a direct impact on performance. Higher job satisfaction improves lecturer performance and weakens the negative effects of burnout. Job satisfaction moderates the relationship between work-life balance and lecturer performance. These findings emphasize the importance of managing burnout and promoting work-life balance to improve job satisfaction and performance among lecturers in the context of Industrial Revolution 4.0. This study contributes to the understanding of the complex relationship between these variables and provides insights for developing strategies to support lecturers’ well-being and performance in the face of technological advances and changes in the work environment